Peran Audit Investigasi untuk Perhitungan Kerugian Negara pada Kasus Korupsi Gubernur yang Ditangani KPK Periode 2013-2022 - Hamdani; Misra, Fauzan (Jurnal Bina Praja, 2023)
Since the Corruption Eradication Commission (KPK) was established in 2003-2022, KPK has handled 20 Governors involved in corruption cases. This study took a sample of 10 governors, or 50% of the number of governors handled by the Corruption Eradication Commission, taking into account the availability of court decision data on the Supreme Court website and population representation from 2013 to 2022. A total of six governors were convicted on charges of bribery-receiving corruption related to local budget management. In handling these cases, it is necessary to calculate state losses by the BPK RI auditors due to the acts of corruption committed. Law Number 15 of 2004 and Law Number 15 of 2006 emphasize the need to examine state financial losses in corruption cases to determine the amount of state losses. These two provisions are not yet binding on Corruption Eradication Commission investigators to ask the Audit Board of the Republic of Indonesia to calculate state financial losses because it is considered that the provisions for requesting an audit are not strictly regulated in Law Number 31 of 1999. This requires harmonization of the regulations governing acts of corruption with those governing the calculation of state losses. Analysis of the charges against the court decision indicates that the calculation of state financial losses by the Audit Board of the Republic of Indonesia (BPK RI) or Finance and Development Supervisory Agency (BPKP) is not used in determining the real and definite amount of state financial losses. The judge fully relied on the amount of bribes received or the amount of corruption enjoyed by the defendant in the indictment as a loss to the state, which must be returned as replacement money. In the indictment, there was no argument for using bribes received as losses to the state, which is an obligation to return to recover the said state losses regulated in Law Number 1 of 2004.